Chemically stable covalent organic framework (COF)-polybenzimidazole hybrid membranes: enhanced gas separation through pore modulation - Biswal, Bishnu P.; Chaudhari, Harshal D.; Banerjee, Rahul; Kharul, Ulhas K. (Chemistry-A European Journal, 2016)
Highly flexible, TpPa-1@PBI-BuI and TpBD@PBI-BuI hybrid membranes based on chemically stable covalent organic frameworks (COFs) could be obtained with the polymer. The loading obtained was substantially higher (50%) than generally observed with MOFs. These hybrid membranes show an exciting enhancement in permeability (about sevenfold) with appreciable separation factors for CO2/N-2 and CO2/CH4. Further, we found that with COF pore modulation, the gas permeability can be systematically enhanced.
Keywords: covalent organic frameworks; Gas separation; membranes; microporous materials; pore modulation